Um estudo comparativo da capacidade de memorização quando obtida por meio digital ou por meio impresso - Silveira, Joaquim José Xavier da (2019)
Introduction: This research observes whether there is a difference in the way information is memorized based on the media it is obtained, printed or digital. Objective: Observe whether memory retention of an information is affected by the media it was obtained – printed or digital, and observe as well if research participants response time, gender and academic area are relevant variables in the process of information apprehension. Method: In order to evaluate these observations, a memory test was developed and applied to Technology and Psychology graduate students at BandTec Digital School and Pontificia Universidade Católica de São Paulo, respectively. 195 students were interviewed, 62 (31,8%) from Psychology (PUC-SP) and 133 (68,2%) from Technology (BandTec Digital School). 103 (52,8%) interviews with content in digital media and 92 (47,2%) with printed content, 117 (60%) test answered by men and 76 (39%) por women, with ages ranging from 16 to 43 years. Conclusion: Based on a quantitative research information, expected hypothesis was achieved: information acquired through printed material is better apprehended than when acquired through digital media. This conclusion provides significant information to educators, giving support to creation of new teaching strategies for the future generations